Virtual water flows and water value in Tunisia: The case of wheat and olive - Souissi, Asma; Chebil, Ali; Mtimet, Nadhem; Thabet, Chokri (Springer, 2019)
Virtual water (VW) refers to freshwater that may be imported or exported via goods that are traded on international markets. VW trade could be considered as a potential solution for water scarcity in countries facing risks of water shortage. This paper aims to assess virtual water content and economic indicators of water use in wheat and olive at various bioclimatic stages in Tunisia. Data was collected from a sample of 113 wheat producers and 123 olive producers, through a survey including technical and economic questions. Olive is chosen as it is the raw material for olive oil, the most strategic exported agricultural product, while wheat is the main imported agricultural product. A water footprint network methodology is used to estimate water productivity and VW flows. Results indicate that by importing wheat, Tunisia is saving up to 1.39 Billion cubic metres (km3) of water. Olive oil exports correspond to 2.44 km3 of exported water. From an economic perspective, the highest irrigation water value is estimated around 1 Tunisian Dinar (TND)/m3 for olive trees in the lower semi-arid regions where it is only around 0.29 TND/m3 for wheat. At the national level, for rain-fed agriculture, olives have higher economic water productivity. Irrigation water value is estimated at 0.51 TND/m3 for olives and 0.40 TND/m3 for wheat. According to our findings, wheat production should be encouraged in the humid and sub-humid regions while olive production should be encouraged in arid and semi-arid areas, in order to generate higher water value in these regions and increase exports revenues of foreign currency.